IMPLEMENTATION OF THE S AVI MODEL TO IMPROVE STUDENT QUALITY AND LEARNING OUTCOMES REVIEW MATERIAL IN CLASS XI ANM 2 SMK NEGERI 1 DLANGGU - Lilik Sulistiani (Sean Institute, 2022)
This research is a class action research (PTK) which aims to determine the improvement in the quality of learning and learning outcomes of class XI ANM 2 students of SMK Negeri 1 Dlanggu through the application of the SAVI model to review material. The research was carried out from January to February 2020 involving 34 students class XI ANM 2 SMK Negeri 1 Dlanggu by applying the SAVI model to Indonesian language lesson review material. The research was carried out for two cycles, each cycle consisting of 4 stages, namely planning, implementing, observing and reflecting. The results showed that through the application of the SAVI model to review material, there was an increase in the quality of learning and student learning outcomes of class XI ANM 2 SMK Negeri 1 Dlanggu. This increase is based on the following indicators: (1) improving teacher performance in learning. Based on the RPP implementation data, it is known that there was an increase in the implementation of the RPP from 3.08 (good) to 3.5 (good) and the percentage of implementation reached 100% in both cycles, (2) student activity showed student-centered learning with the percentage of activity reaching 85.11% in the first cycle rising to 95.56% in the second cycle, (3) student responses in both cycles were positive. The majority of students expressed interest in the application of the SAVI learning model and were interested if the same model was applied to other materials, and (4) learning outcomes showed an increase from 50 % in the pre-cycle to 76.92% in the first cycle and to 88.46 % in the second cycle. This shows the mastery of classical learning outcomes achieved in the second cycle